INTEGRATED INTELLIGENT SAFETY SYSTEMS (Perner's Contacts, 2016)
The aim of this paper is to introduce vehicle safety. Introduced will present intelligent vehicle safety systems, which are used in today's advanced intelligent vehicles. Progress in technology and information systems open up new possibilities in vehicle safety, which can reduce traffic accidents.